Advantages in orthopaedic implant infection diagnostics by additional analysis of explants - Höppchen, Arnold; Miethke, Thomas; Landua, Nadine; Obertacke, Udo (International orthopaedics, 2025)
Purpose Implant-associated infections are the most challenging complication in orthopaedics and trauma surgery as they often lead to long courses of illness and are a financial burden for the healthcare system. There is a need for fast, simple, and cheap identification of pathogens but the ideal detection method was not found yet. The work aims to test whether the detection of pathogens culturing the removed implant is more successful than from simultaneously taken tissue samples or punction fluid. Methods Implants were removed due to infection, irritation, or loosening. Tissue samples and joint fluids were processed for bacterial growth in sterile conditions. Samples were incubated and checked for growth. Bacterial identification and antibiotic sensitivity testing were performed. Data were anonymized, and statistical analysis was done using Excel and SAS, employing tests like Shapiro-Wilk, Mann-Whitney-U, and Kruskal-Wallis. Ethical approval was obtained for this study. Results Between February 2018 and April 2019, a total of 163 patients (175 cases) underwent orthopaedic implant removal for various reasons. 30 cases were not usable or analyzable due to missing or damaged reference material, so 145 cases could be evaluated due to study protocol. The range of detected bacteria was as expected and included low-virulent bacteria such as Micrococcus luteus and Corynebacteria. Pathogen detection by culture of the the explant´s was more sensitive (84.83%) than pathogen detection from tissue samples and punction fluid (64.14%, p<0.0001). Comorbidities did not play any role in the quality of detection but prior antibiotic treatment did influence the results of tissue diagnostics. Conclusion This study showed with a higher frequency of bacterial detection of orthopedic explant´s surface compared to tissue samples or punction fluid. This may reduce the number of samples and cost but enhances the quality of orthopaedic implant-related infection diagnostics.